Myelin loss and oligodendrocyte pathology in white matter tracts following traumatic brain injury in the rat. Issue 1 (5th March 2013) - Flygt, J.; Djupsjö, A.; Lenne, F.; Marklund, N.
Abstract Axonal injury is an important contributor to the behavioral deficits observed following traumatic brain injury (TBI). Additionally, loss of myelin and/or oligodendrocytes can negatively influence signal transduction and axon integrity. Apoptotic oligodendrocytes, changes in the oligodendrocyte progenitor cell (OPC) population and loss of myelin were evaluated at 2, 7 and 21 days following TBI. We used the central fluid percussion injury model (n = 18 and three controls) and the lateral fluid percussion injury model (n = 15 and three controls). The external capsule, fimbriae and corpus callosum were analysed. With Luxol Fast Blue and RIP staining, myelin loss was observed in both models, in all evaluated regions and at all post‐injury time points, as compared with sham‐injured controls (P ≤ 0.05). Accumulation of β‐amyloid precursor protein was observed in white matter tracts in both models in areas with preserved and reduced myelin staining. White matter microglial/macrophage activation, evaluated by isolectin B4 immunostaining, was marked at the early time points. In contrast, the glial scar, evaluated by glial fibrillary acidic protein staining, showed its highest intensity 21 days post‐injury in both models. The number of apoptotic oligodendrocytes, detected by CC1/caspase‐3 co‐labeling, was increased in both models in all evaluated regions. Finally, the numbers of OPCs, evaluated with the markers Tcf4 and Olig2, were increased from day 2 (Olig2) or day 7 (Tcf4) post‐injury (P ≤ 0.05). Our results indicate that TBI induces oligodendrocyte apoptosis and widespread myelin loss, followed by a concomitant increase in the number of OPCs. Prevention of myelin loss and oligodendrocyte death may represent novel therapeutic targets for TBI.